2017
DOI: 10.1097/pra.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Cannabinoids Use in Elderly Patients

Abstract: Synthetic cannabinoids, also known as “Spice” or “K2,” are a group of recreational substances that elicit cannabimimetic effects similar to delta (9)-tetrahydrocannabinol, the primary psychoactive constituent in cannabis. They are becoming a public health concern because they are toxic and they are not detected by standard urine screening tests. The largest group of users of synthetic cannabinoids are adolescent males who are polysubstance users; however, no data are available concerning use of synthetic canna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…The full text of remaining 216 papers was searched, and a further 192 papers excluded due to not fulfilling the inclusion criteria (Fig 1). After abstraction and full text screening, a total of 24 articles were selected for review: 2 toxicology reports (Monte et al, 2017;Waugh et al, 2016), 4 casecontrol studies (Altintas et al, 2016;Bassir Nia et al, 2016;Shalit et al, 2016;Welter et al, 2017), 3 cross-sectional analyses (Glue et al, 2013;Manseau et al, 2017;Vallersnes et al, 2016) and 15 case reports (Barcelo et al, 2017;Benford and Caplan, 2011;Coppola and Mondola, 2017;Hurst et al, 2011;Johnson et al, 2011;Mahgoub and Young, 2017;Meijer et al, 2014;Muller et al, 2017;Oliveira et al, 2017;Oluwabusi et al, 2012;Ozer et al, 2016;Roberto et al, 2016;Rojek et al, 2017;Samaan et al, 2016; Van der Veer and Friday, 2011) ( Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…The full text of remaining 216 papers was searched, and a further 192 papers excluded due to not fulfilling the inclusion criteria (Fig 1). After abstraction and full text screening, a total of 24 articles were selected for review: 2 toxicology reports (Monte et al, 2017;Waugh et al, 2016), 4 casecontrol studies (Altintas et al, 2016;Bassir Nia et al, 2016;Shalit et al, 2016;Welter et al, 2017), 3 cross-sectional analyses (Glue et al, 2013;Manseau et al, 2017;Vallersnes et al, 2016) and 15 case reports (Barcelo et al, 2017;Benford and Caplan, 2011;Coppola and Mondola, 2017;Hurst et al, 2011;Johnson et al, 2011;Mahgoub and Young, 2017;Meijer et al, 2014;Muller et al, 2017;Oliveira et al, 2017;Oluwabusi et al, 2012;Ozer et al, 2016;Roberto et al, 2016;Rojek et al, 2017;Samaan et al, 2016; Van der Veer and Friday, 2011) ( Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Nach Einstellung des Konsums können Entzugserscheinungen auftreten in Form von verbal geäußertem Drogendrang, Hypertonie, Nausea, Tremor, Albträumen und Diaphorese. Im Extremfall kann es bei einmaliger Einnahme von SCRAs und ohne vorbestehende psychiatrische Erkrankungen oder suizidale Absichten zu schwerster Selbsttraumatisierung mit letalem Ausgang kommen [30,38,52].…”
Section: Komplikationen Und Unerwünschte Wirkungenunclassified
“…Although there have been a number of case reports focusing on the presence of psychotic signs and symptoms associated with SC use (Hurst et al, 2011; Mahgoub and Young, 2017; Van Der Veer and Friday, 2011), there are few case control studies that have analysed the characteristics of SC users and how SC use impacts upon prognostic factors such as length of stay in psychiatric services, and none in a UK-specific sample. A US-based study of patients admitted to a dual diagnosis ward (with drug use and mental-health problems) reported that patients who took SCs were more likely to have a psychotic presentation, and were more likely to have agitation as part of their presentation, were less likely to be Caucasian and had increased length of hospital stay (Bassir Nia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%